Social postmodernism beyond identity politics - Nicholson, Linda J.; Seidman, Steven (Cambridge cultural social studies, 1995)
Social Postmodernism defends a postmodern perspective anchored in the politics of the new social movements. The volume preserves the focus on the politics of the body, race, gender, and sexuality as elaborated in postmodern approaches. But these essays push postmodern analysis in a particular direction: toward a social postmodernism which integrates the micro-social concerns of the new social movements with an institutional and cultural analysis in the service of a transformative political vision